Letter (copy) - Carthy, A. E.
025a-0012-001 International. AC/DT/404. 1st January, 1941. Mr. S. Arenaza, SS "Santiago", Milford Haven. Dear Mr. Arenaza, I was glad to hear from your sister of your success in finding employment and pleased to learn from your letter what a fine post it is you have got. Thanks for the information about Larraberti and Prat. I have passed on to Mr. Tewson your thanks for the assistance which you have received, and with best wishes for the future, yours sincerely, International Department 292/946/25a/12